IMPROVING READING COMPREHENSION OF THE EIGHTH-GRADE STUDENTS OF SMPN 4 SUKAWATI IN ACADEMIC YEAR 2022/2023 THROUGH RAP - Dinda Paramitha Wibawa; Anak Agung Putu Arsana; Ni Wayan Krismayani (Academic Journal on English Studies (AJOES), 2023)
The study aims at figuring out whether the subjects’ reading comprehension can be improved through the RAP strategy. The subjects were the eighth-grade students of SMPN 4 Sukawati. The strategy in this present study which have three elements such as: Read, Ask, Put. Thus, to achieve the objective the researcher was conducted classroom action research design. The data which were needed for the present study were collected through RAP strategy in two cycles and the obtained data was analyzed quantitively from the pre-test, post-test I and post-test II; then qualitatively from the questionnaire. In conclusion, it could be concluded that reading comprehension of the eighth-grade students of SMPN 4 Sukawati in academic year 2022/2023 could be improved through RAP strategy.